Post-World War II Education Reform in Japan - Ong, Susy (Journal of Strategic and Global Studies, 2020)
The rise of Japan after the defeat in World War II became the center of world admiration, including us in Indonesia. Human resources development through education has become the main key to the success of Japan. This certainly can be a reference for us in formulating human resources development policies in the future. We often feel amazed at the seriousness of the Japanese government in dealing with education problems. However, we also tend to ignore various facts related to it. For example, after the defeat of the war, Japanese academics and bureaucrats immediately conducted introspection and research to find out the cause of the defeat. From the results of this research, it was concluded that there were fatal errors in education policies and philosophies so far; departing from this understanding, a significant revision of the education law was immediately carried out. In other words, the Japanese government not only pays attention to education but they also completely overhaul educational policies. Japan lost the war against the United States. Consequently, for the following 7 years, 1945-1952, Japan was occupied by the United States of America, who had ordered Japan to change all policies, including educational policies. In this paper, we will look at what changes in the philosophical foundation and policy changes, as well as how the discussion process until the formulation and enactment of several new education laws, and what criticisms and expectations are implied in the education law.